A Study on the Effect of Hollow Tubular Flange Sections on the Behavior of Cold-Formed Steel Built-Up Beams - Balaji Shanmugam; Manikandan Palanisamy; Paul O. Awoyera; Senthilnathan Chinnasamy; Mahalakshmi Subramaniam (Advances in Civil Engineering)
This paper deals with a study conducted on flexural behavior of cold-formed steel built-up I-beams with hollow tubular flange sections. There were two types of test sections, namely, built-up sections that were assembled with either stiffened or unstiffened channels coupling back-to-back at the web and a hollow tubular rectangular flange at the top and bottom of the web to form built-up I-beam. The flexural behavior along with the strength and failure modes of the built-up sections was examined using the four-point loading system. Nonlinear finite element (FE) models were formulated and validated with the experimental test results. It was observed that the developed FE models had precisely predicted the behavior of built-up I-beams. Further, the verified FE models were used to conduct a detailed parametric study on cold-formed steel built-up beam sections with respect to thickness, depth, and yield stress of the material. The flexural strength of the beams was designed using the direct strength method as specified in American Iron and Steel Institute (AISI) for the design of cold-formed steel structural members and was compared with the experimental results and the failure loads predicted from FE models. Since the results were not conservative, a new customized design equation had been mooted and delineated in the study for determining the flexural strength of cold-formed steel built-up beams with hollow tubular flange sections.